Effect of Impulse Polarity on a New Grounding Device with Spike Rods (GDSR) - Abdul Wali Abdul Ali; Nurul Nadia Ahmad; Normiza Mohamad Nor (Energies, 2020)
The characterizations of grounding systems subjected to high impulse conditions are known to be dependent on the polarity, current to peak time and discharge time, as well as the electrical properties of the soil, and the grounding electrodes themselves. It is therefore important to investigate the behavior of grounding systems under high impulse conditions under negative impulse polarity, and compare it with positive impulse polarity results. Experimental test results for the same grounding systems installed with various earth electrodes at several sites under positive impulse polarity have previously been presented. In comparison, this paper presents the results of negative impulse polarity injected on the same grounding systems. It is found that a significant difference between positive and negative impulse polarities is observed for the grounding systems installed at high soil resistivity.